Answer:
−
6
−
2
0
=
−
2
+
4
(
1
−
3
)
−
6
−
2
0
=
−
2
+
4
(
−
3
+
1
)
2
Distribute
−
6
−
2
0
=
−
2
+
4
(
−
3
+
1
)
−
6
−
2
0
=
−
2
−
1
2
+
4
3
Combine like terms
−
6
−
2
0
=
−
2
−
1
2
+
4
−
6
−
2
0
=
−
1
4
+
4
4
Add
2
0
20
20
to both sides of the equation
−
6
−
2
0
=
−
1
4
+
4
−
6
−
2
0
+
2
0
=
−
1
4
+
4
+
2
0
5
Simplify
Add the numbers
Add the numbers
−
6
=
−
1
4
+
2
4
6
Add
1
4
14p
14p
to both sides of the equation
−
6
=
−
1
4
+
2
4
−
6
+
1
4
=
−
1
4
+
2
4
+
1
4
7
Simplify
Combine like terms
Combine like terms
8
=
2
4
8
Divide both sides of the equation by the same term
8
=
2
4
8
8
=
2
4
8
9
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=
3
Solution
=3
Step-by-step explanation:
please give me brainliest